Chloropicophyceae, a new class of picophytoplanktonic prasinophytes. Issue 1 (December 2017) - Lopes dos Santos, Adriana; Pollina, Thibaut; Gourvil, Priscillia; Corre, Erwan; Marie, Dominique; Garrido, José; Rodríguez, Francisco; Noël, Mary-Hélène; Vaulot, Daniel; Eikrem, Wenche
Abstract Prasinophytes are a paraphyletic group of nine lineages of green microalgae that are currently classified either at the class or order level or as clades without formal taxonomic description. Prasinophyte clade VII comprises picoplanktonic algae that are important components of marine phytoplankton communities, particularly in moderately oligotrophic waters. Despite first being cultured in the 1960s, this clade has yet to be formally described. Previous phylogenetic analyses using the 18S rRNA gene divided prasinophyte clade VII into three lineages, termed A, B and C, the latter formed by a single species, Picocystis salinarum, that to date has only been found in saline lakes. Strains from lineages A and B cannot be distinguished by light microscopy and have very similar photosynthetic pigment profiles corresponding to the prasino-2A pigment group. We obtained phenotypic and genetic data on a large set of prasinophyte clade VII culture strains that allowed us to clarify the taxonomy of this important marine group. We describe two novel classes, the Picocystophyceae and the Chloropicophyceae, the latter containing two novel genera, Chloropicon andChloroparvula, and eight new species of marine picoplanktonic green algae.